1602g Shiftwork, automated vehicles, and functional impairments in transportation. (24th April 2018) - Fisher, D; Popkin, S; Lohrenz, M; Davies-Schrils, K; Moore, D
Abstract : Introduction: Shiftwork has been linked to functional impairments such as fatigue and distraction that increase crash risk. Automated vehicles may decrease these risk factors. Simultaneously, automated vehicles will allow a broader range of 'drivers' to operate the vehicle such as those with cognitive and physical impairments, creating additional benefits and impacts to shiftworking drivers with such impairments. We have developed a conceptual model of how automation at all levels can be used to reduce the impacts of shiftwork on functional impairments in transportation. Methods: Over 100 articles were reviewed in the areas of shiftwork, automation, and functional impairment using established key words and recognised search domains. Central to the understanding of the relations among shiftwork, automation and functional impairments is knowledge of how drivers use, misuse, disuse and are abused by automation. Results: The result of the literature search and its analysis is a conceptual model which clarifies how shiftwork impacts the use, misuse and disuse of automation at each level, and how those impacts affect drivers with different types and levels of functional impairment. Existing research suggests that long shifts can lead to an increase in the misuse of automation, with fatigued and distracted drivers over-trusting automation. This effect will be magnified for those with cognitive impairments. However, systems are now deployed that can detect driver state such as fatigue and distraction, and could potentially communicate with an automatic driving suite and intervene when the driver is fatigued or distracted. Discussion: The conceptual model creates a roadmap for future research, applications and regulations that various stakeholders can use to improve the safety and well-being of shiftworkers.